PENGARUH KOMPETENSI KEPALA SEKOLAH DAN BUDAYA ORGANISASI SEKOLAH TERHADAP KINERJA KEPALA SEKOLAH DASAR DI KECAMATAN WONOSALAM KABUPATEN DEMAK - MUHAJIR MUHAJIR (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study uses a quantitative approach by processing and analyzing research data into meaningful data. The population of this research is all civil servant teachers of public elementary schools in Wonosalam District, Demak Regency, totaling 245 people, obtained a sample of 71 people using proportional random sampling technique. Collecting data using a questionnaire method. Analysis of the data used is descriptive analysis, prerequisite test and hypothesis testing which includes correlational testing, simple regression and multiple regression and determination. From the results of the study, it can be seen that the average principal competency score is 126.82 including the high category, the average school organizational culture score obtained is 71.62 including the high category and the average principal score is 133.28 included in the high category. From the hypothesis test, there is a positive and significant influence of the principal's competence on the principal's performance with a contribution of 47.8%. There is a positive and significant influence of school organizational culture with a contribution of 18.6%. And there is a positive and significant influence on the principal's competence and school organizational culture together on the principal's performance with a contribution of 51%. On the basis of this research, it is recommended that: (1) primary school principals actively participate in education and training activities, attend workshops on leadership, attend seminars, actively participate in KKKS and continue their studies. (2) The head of the UPTD of the Department of Education, Youth and Sports, Wonosalam District, should provide facilities for principals of public elementary schools to attend education and training, workshops, seminars, KKKS and continue their studies. So that the performance of the principal of public elementary schools in Wonosalam District, Demak Regency further increases and ultimately can improve the quality of education. ABSTRAKPenelitian ini menggunakan pendekatan kuantitatif dengan mengolah dan menganalisa data hasil penelitian menjadi sebuah data yang bermakna. Populasi penelitian ini adalah seluruh guru PNS sekolah dasar negeri di Kecamatan Wonosalam Kabupaten Demak, yang berjumlah 245 orang, diperoleh sampel sebanyak 71 orang dengan menggunakan teknik proportional random sampling. Pengumpulan data menggunakan metode kuesioner. Analisis data yang digunakan adalah analisis deskriptif, uji prasyarat dan uji hipotesis yang meliputi pengujian korelasional, regresi sederhana dan regresi ganda dan determinasi. Dari hasil penelitian dapat diketahui bahwa rata-rata perolehan skor kompetensi kepala sekolah 126,82 termasuk kategori tinggi, rata-rata perolehan skor budaya organisasi sekolah diperoleh skor 71,62 termasuk kategori tinggi dan rata-rata skor perolehan kinerja kepala sekolah adalah 133,28 termasuk kategori tinggi. Dari uji hipotesis terdapat pengaruh yang positif dan signifikan kompetensi kepala sekolah terhadap kinerja kepala sekolah dengan kontribusi sebesar 47,8%. Terdapat pengaruh positif dan signifikan budaya organisasi sekolah dengan kontribusi sebesar 18,6%. Dan terdapat pengaruh positif dan signifikan kompetensi kepala sekolah dan budaya organisasi sekolah secara bersama-sama terhadap kinerja kepala sekolah dengan kontribusi sebesar 51%. Atas dasar penelitian tersebut maka disarankan: (1) kepala sekolah dasar aktif mengikuti kegiatan pendidikan dan pelatihan, mengikuti workshop tentang kepemimpinan, mengikuti seminar-seminar, aktif mengikuti KKKS dan melanjutkan studynya. (2) Hendaknya kepala UPTD Dinas Pendidikan Pemuda dan Olah Raga Kecamatan Wonosalam agar memberikan fasilitas bagi kepala sekolah dasar negeri untuk mengikuti pendidikan dan pelatihan, workshop, seminar, KKKS dan melanjutkan studynya. Sehingga kinerja kepala sekolah dasar negeri di Kecamatan Wonosalam Kabupaten Demak lebih meningkat dan akhirnya dapat meningkatkan mutu pendidikan.